A method for preparing cemented backfill materials based on response surface methodology and composite excitation of coal gasification slag

By using response surface methodology to prepare composite activators for treating coal gasification slag and coal gangue, the shortage and high cost of backfill materials caused by the low activity of coal gasification slag were solved, realizing the preparation of environmentally friendly cemented backfill materials and ensuring sustainable development.

CN117069453BActive Publication Date: 2025-10-31TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202311066000.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-10-31
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

The volcanic ash activity of coal gasification slag is low, which leads to a shortage and high cost of cemented backfill materials in backfill mining, and the accumulation of coal gasification slag occupies land and pollutes the environment.

Method used

A composite activator was prepared using response surface methodology. Coal gasification slag and coal gangue were processed by ball milling and crushing, and combined with cement, aggregates and activator to prepare a high-strength cemented filling material.

Benefits of technology

The effective use of coal gasification slag has solved the problems of shortage and high cost of cemented backfill materials, reduced environmental pollution and land occupation, and achieved sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117069453B_ABST
    Figure CN117069453B_ABST
Patent Text Reader

Abstract

The purpose of this invention is to provide a method for preparing cemented backfill materials based on response surface methodology using composite activating coal gasification slag. This method belongs to the field of mining engineering technology. Based on sorting and removing impurities from the coal gasification slag and drying it, the invention obtains ultrafine powder of the coal gasification slag for preparing the backfill material through ball milling. Then, coal gangue is crushed and screened using a crusher to obtain coarse, medium, and fine aggregates for the backfill material. Finally, cement, ultrafine coal gasification slag powder, coal gangue aggregate, activator, and water are mixed evenly to prepare the cemented backfill material. This invention not only solves the problem of low activity of coal gasification slag volcanic ash but also effectively controls the shortage of cemented backfill materials and high backfilling costs during cemented backfill mining, ensuring sustainable development. Furthermore, it effectively utilizes the widely accumulated coal gasification slag, reducing pollution and large-scale land occupation of the surrounding environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of mining engineering technology, specifically relating to a method for preparing cemented backfill materials based on response surface methodology for composite excitation of coal gasification slag. Background Technology

[0002] Coal is one of the world's three major traditional energy sources, holding a vital position in the global energy structure. However, the direct combustion of coal causes environmental pollution and contributes to global warming. Coal gasification technology, as an important clean coal utilization technology, has developed rapidly, boasting high efficiency, low emissions of carbon dioxide, sulfur dioxide, and nitrogen oxides, and high flexibility. However, the gasification process generates a large amount of solid waste—gasification slag. The accumulation of large quantities of gasification slag not only wastes significant land resources and incurs excessive costs for the construction and management of storage sites, but also easily pollutes the surrounding soil and environment. The main components of gasification slag include silicon dioxide, calcium oxide, and aluminum oxide, possessing potential pozzolanic activity. However, the large amount of silicon and aluminum oxides in gasification slag exists in a glassy structure and cannot directly participate in hydration reactions. Therefore, the rational and economical activation of gasification slag and its large-scale reuse has become an urgent problem to be solved.

[0003] Backfilling mining is a mining technique that uses cementitious materials such as cement, coal gangue, and fly ash to fill goaf areas. However, due to the redevelopment and limited availability of these materials, their quantity is insufficient to meet the demands of backfilling mining. Therefore, there is an urgent need for a new material that is low-cost, widely available, and meets strength requirements to address these issues and ensure the stability of the backfill material.

[0004] In summary, backfilling mining faces problems such as high raw material costs and limited sources, while coal gasification slag has low recycling rates, occupies space, and pollutes the environment. After simple processing, coal gasification slag can replace cement as a cementing material for backfilling mining. Combining the two not only solves the shortage of backfilling materials, but also makes full use of coal gasification slag, turning it from waste into treasure. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing cemented backfill materials based on response surface methodology for composite excitation of coal gasification slag, in order to solve the problem of low activity of coal gasification slag volcanic ash, effectively control the shortage of cemented backfill materials and high backfilling costs during backfilling mining, ensure sustainable development, and effectively utilize the widely accumulated coal gasification slag, thereby reducing pollution and large-scale land occupation.

[0006] The present invention adopts the following technical solution:

[0007] A method for preparing cemented backfill materials based on response surface methodology using composite-induced coal gasification slag includes the following steps:

[0008] The first step is to collect the solid residue after coal gasification, sort and clean the dust and impurities in the coal gasification residue, and then dry it in the sun. After drying, it is ground into ultrafine powder using a planetary ball mill to obtain coal gasification residue ultrafine powder.

[0009] The second step is to collect coal gangue and crush it with a jaw crusher to make the particle size less than 15mm. Then, a vibrating screen is used to screen the crushed coal gangue to obtain fine aggregate of 0-5mm, medium aggregate of 5-10mm and coarse aggregate of 10-15mm.

[0010] The third step is to add a composite activator to the ultrafine powder of coal gasification slag and stir it evenly.

[0011] The fourth step involves mixing cement with fine aggregate, medium aggregate, coarse aggregate, and ultrafine coal gasification slag containing a composite activator in a specific ratio, stirring until homogeneous, adding water and stirring until homogeneous to obtain the cemented filling material.

[0012] Furthermore, the planetary ball mill described in the first step operates at a speed of 500 r / min and a milling time of 100 min, resulting in an ultrafine powder of coal gasification slag with a specific surface area greater than or equal to 400 m². 2 / kg.

[0013] Furthermore, the composite activator mentioned in the third step includes a response surface methodology-based design, with each factor level being 0.5%-1.5% carbide slag, 0%-2% desulfurized gypsum, 2%-3% sodium sulfate, and 4%-10% water glass, accounting for 1% of the mass of the ultrafine coal gasification slag powder.

[0014] Furthermore, in step four, the weight percentages of cement, fine aggregate, medium aggregate, coarse aggregate, and ultrafine coal gasification slag containing composite activator are as follows: cement: 10%, fine aggregate: 12%, medium aggregate: 4%, coarse aggregate: 4%, ultrafine coal gasification slag containing activator: 70%, and the mass concentration of the cementitious backfill material formed after adding water is 80%.

[0015] Furthermore, the cement mentioned in step four is ordinary PO 42.5 silicate cement.

[0016] The beneficial effects of this invention are as follows:

[0017] This invention, based on the sorting, impurity removal, and drying of coal gasification slag, obtains ultrafine powder of coal gasification slag for preparing backfill materials through ball milling. Then, coal gangue is crushed and screened using a crusher to obtain coarse, medium, and fine aggregates for preparing the backfill material. Finally, cement, ultrafine coal gasification slag powder, coal gangue aggregate, activator, and water are mixed evenly to prepare the cemented backfill material. This invention not only solves the problem of low activity of coal gasification slag volcanic ash but also effectively controls the shortage of cemented backfill materials and high backfill costs during cemented backfill mining, ensuring sustainable development. Furthermore, it effectively utilizes the widely accumulated coal gasification slag, reducing pollution and large-scale land occupation of the surrounding environment. Attached Figure Description

[0018] Figure 1 It is the response surface of the effect of calcium carbide slag content and desulfurized gypsum content on 28-day compressive strength;

[0019] Figure 2 It is the response surface of the effect of calcium carbide slag content and sodium sulfate content on 28-day compressive strength;

[0020] Figure 3 It is the response surface of the effect of calcium carbide slag content and water glass content on 28-day compressive strength;

[0021] Figure 4 It is the response surface of the effect of desulfurized gypsum content and sodium sulfate content on 28-day compressive strength;

[0022] Figure 5 It is the response surface of the effect of desulfurized gypsum content and water glass content on 28-day compressive strength;

[0023] Figure 6 It is the response surface of the effect of sodium sulfate content and water glass content on 28-day compressive strength;

[0024] Figure 7 It is a scatter plot of actual values ​​and predicted values;

[0025] Figure 8 It is a scatter plot of actual values ​​and residuals;

[0026] Figure 9 It is a scatter plot of predicted values ​​and residuals. Detailed Implementation

[0027] A method for preparing cemented backfill materials based on response surface methodology using composite-induced coal gasification slag includes the following steps:

[0028] The first step is to collect the solid residue after coal gasification, sort and clean the dust and impurities in the coal gasification residue, and then dry it in the sun. After drying, it is ground into ultrafine powder using a planetary ball mill to obtain coal gasification residue ultrafine powder.

[0029] The second step is to collect coal gangue and crush it with a jaw crusher to make the particle size less than 15mm. Then, a vibrating screen is used to screen the crushed coal gangue to obtain fine aggregate of 0-5mm, medium aggregate of 5-10mm and coarse aggregate of 10-15mm.

[0030] The third step is to add a composite activator to the ultrafine powder of coal gasification slag and stir it evenly.

[0031] The fourth step involves mixing cement with fine aggregate, medium aggregate, coarse aggregate, and ultrafine coal gasification slag containing a composite activator in a specific ratio, stirring until homogeneous, adding water and stirring until homogeneous to obtain the cemented filling material.

[0032] Example 1

[0033] This embodiment provides a method for preparing cemented filling materials based on response surface methodology and composite excitation of coal gasification slag.

[0034] Step 1: Collect waste coal gasification slag from a chemical plant in Shaanxi Province, sort and clean it to remove dust, stones and other impurities, and then dry it.

[0035] Step two: The dried coal gasification slag is ball-milled to obtain ultrafine coal gasification slag powder for filling material, with a specific surface area of ​​440 m². 2 / kg;

[0036] Step 3: Use a jaw crusher to crush the coal gangue, and crush the coal gangue with a particle size greater than 15mm again so that the particle size is less than 15mm.

[0037] Step 4: Use a vibrating screen to screen the crushed coal gangue to obtain coarse aggregate, medium aggregate and fine aggregate for preparing the filling material, wherein the fine aggregate has a particle size of 0-5mm, the medium aggregate has a particle size of 5-10mm and the coarse aggregate has a particle size of 10-15mm.

[0038] Step 5: Add a composite activator of carbide slag, desulfurization gypsum, sodium sulfate, and water glass to the ultrafine powder of coal gasification slag obtained above and stir evenly.

[0039] Step 6: After uniformly mixing the cement with the fine aggregate, medium aggregate, coarse aggregate and ultrafine coal gasification slag containing carbide slag, water is added to prepare the backfill material. The weight ratio of each solid component is as follows: cement: 10%, fine aggregate: 12%, medium aggregate: 4%, coarse aggregate: 4%, ultrafine coal gasification slag containing composite activator: 70%. The mixture is uniformly mixed, and then water is added to form a cemented backfill material with a mass concentration of 80%.

[0040] The coal gasification slag cemented filling material prepared in Example 1 was cast into a cylinder of 50mm×100mm. A blank sample was used as a control (28-day strength of 8.42MPa). After 24 hours, the sample was demolded and placed in a curing room at a temperature of (20±2℃) and a relative humidity of 95% for 28 days. The uniaxial compressive strength of the specimens was measured after curing for 3 days, 7 days, 14 days, and 28 days.

[0041] 1. Response surface methodology and results

[0042] A four-factor, three-level response surface methodology was established, and the factor level table is shown in Table 1.

[0043] Table 1. Levels of various factors in the response surface of the composite activator

[0044]

[0045] A total of 29 sets of experiments were conducted, with the following influencing factors: calcium carbide slag content (%), desulfurized gypsum content (%), sodium sulfate content (%), and water glass content (%). The 28-day compressive strength was used as the evaluation index. The design combinations and their corresponding results are shown in Table 2.

[0046] Table 2. Response surface design and experimental results of composite activators

[0047]

[0048] 2. Regression equation fitting and analysis of variance

[0049] A regression equation was established by fitting data to the 28-day compressive strength Y using the following independent variables: calcium carbide slag content (A), desulfurized gypsum content (B), sodium sulfate content (C), and water glass content (D).

[0050]

[0051] The analysis of variance is shown in Table 3. According to Table 3, the P-value of the regression equation model is extremely significant, indicating that the model has a good fit and the experimental method is feasible; the P-value of the lack-of-fit term is not significant, indicating that the model error is small; the larger the F-value of a factor and the smaller the P-value, the greater the influence of that factor on the results.

[0052] Table 3. Variance results of response surface experiments

[0053]

[0054] Note: **: P < 0.01 is considered significant;

[0055] 3. Response Surface Analysis

[0056] Response surface methodology (RSM) plots are used to analyze target values ​​and independent variables. Together, they form a three-dimensional spatial diagram. By analyzing the three-dimensional RSM plot, the influence of different factors on the target response value can be significantly reflected, thereby obtaining the role of the corresponding interaction factors of each factor in the response process. The effectiveness of the influence can be determined by the response value parameters under different conditions.

[0057] Response surface experimental surface plot as shown Figure 1-6 As shown, Figure 7 This is a scatter plot of the predicted and actual values ​​in this experiment. Figure 8 This is a plot of the normal probability distribution of the residuals. Figure 9 The scatter plot of residuals versus predicted values ​​shows a good linear relationship in the data distribution.

[0058] 4. Predictive Model Validation Experiment

[0059] The optimal results were obtained through response surface methodology: 0.97% calcium carbide slag, 2% desulfurized gypsum, 3% sodium sulfate, and 10% water glass. After 55 iterations of optimization, a 28-day compressive strength of 12.46 MPa was achieved. Three experiments were conducted to verify this, yielding a 28-day compressive strength of 11.64 MPa, which deviated from the theoretical value by 0.82 MPa, demonstrating the high reliability of the extraction process obtained from the response surface methodology.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing cemented backfill material based on response surface methodology using composite-induced coal gasification slag, characterized in that: Includes the following steps: The first step involves collecting the solid residue after coal gasification, sorting and cleaning the dust and impurities from the coal gasification slag, and then drying it. After drying, it is ground into ultrafine powder using a planetary ball mill to obtain ultrafine coal gasification slag powder with a specific surface area greater than or equal to 400 m². 2 / kg; The second step is to collect coal gangue and crush it with a jaw crusher to make the particle size less than 15mm. Then, a vibrating screen is used to screen the crushed coal gangue to obtain fine aggregate of 0-5mm, medium aggregate of 5-10mm and coarse aggregate of 10-15mm. The third step is to add a composite activator to the ultrafine coal gasification slag powder and stir it evenly; the composite activator is composed of 0.5%-1.5% carbide slag, 0%-2% desulfurized gypsum, 2%-3% sodium sulfate, and 4%-10% water glass, accounting for 0.5%-1.5% of the mass of the ultrafine coal gasification slag powder. The fourth step is to mix cement with fine aggregate, medium aggregate, coarse aggregate and ultrafine coal gasification slag containing composite activator in proportion, stir evenly, add water and stir evenly to obtain cemented filling material. The weight percentages of the cement, fine aggregate, medium aggregate, coarse aggregate, and ultrafine coal gasification slag containing composite activator are as follows: cement: 10%, fine aggregate: 12%, medium aggregate: 4%, coarse aggregate: 4%, ultrafine coal gasification slag containing activator: 70%, and the mass concentration of the cementitious backfill material formed after adding water is 80%.

2. The method for preparing cemented backfill material based on response surface methodology and composite excitation of coal gasification slag according to claim 1, characterized in that: The planetary ball mill mentioned in the first step has a rotation speed of 500 r / min and a ball milling time of 100 min.

3. The method for preparing cemented backfill material based on response surface methodology and composite excitation of coal gasification slag according to claim 1, characterized in that: The composite activator described in the third step is designed based on response surface methodology.

4. The method for preparing cemented backfill material based on response surface methodology and composite excitation of coal gasification slag according to claim 1, characterized in that: The cement mentioned in step four is ordinary PO 42.5 silicate cement.

Citation Information

Patent Citations

  • Alkali-activated high-water-content mine filling material based on synergism of multiple solid wastes and preparation method thereof

    CN113292305A

  • Multi-slag solid alkaline cement and preparation method thereof

    CN114507043A

Cited By

  • Filling material with synergy of coal gasification slag graded utilization and CO2 mineralization and preparation method of filling material

    CN121470859A

  • A backfill material for graded utilization of coal gasification slag and synergistic CO2 mineralization, and its preparation method.

    CN121470859B